Upcycling textile wastes: challenges and innovations. Issue 2 (3rd April 2021) - Kamble, Zunjarrao; Behera, Bijoya Kumar
Abstract: Food, shelter and clothing are three basic necessities of life. Textiles are necessary for human beings to cover and protect the body from different weather conditions. In the household, textiles are used in carpeting, furnishing, window shades, towels, table covers, bed sheets, handkerchiefs, cleaning devices and in art. In the workplace, they are used in industrial and scientific processes such as tents, flags, nets, kites, sails, parachutes and filtering. Technical textiles are used for industrial purposes – for automotive applications, medical textiles (e.g. implants, personal protective equipment and clothing, wound care and compression), geotextiles (stabilisation; reinforcement of embankments), agrotextiles, protective clothing (e.g. against heat and radiation for fire-retardant clothing, against molten metals for welders, stab protection, and bullet proof vests), packaging and for making advanced materials like composites. In the case of apparel, 'fast fashion' has led to increased consumption of textiles and thereby increased textile waste, which poses a great challenge to today's world in terms of unsustainable disposal. Textile waste has also become a greater threat to modern society mainly because of constant growth in the production and consumption of non-biodegradable synthetic fibres. Unless adequately treated, textile wastes from hospitals may carry hazardous pathogens whilst many fashion clothing items contain non-bio-degradable chemicals which can create havoc in the environment following their disposal, so the recycling of waste textiles has grown in importance. Many studies have shown that much of what would otherwise become waste textiles could be successfully upcycled to produce value-added products. However, the true potential of waste textiles is not yet realized due to many reasons, such as the lack of an adequate textile waste management system, the complexity of the required treatment of some types of textile materials (fibre blends or mixed-fibre textiles) and poor organisation and control over supply chains. This issue of Textile Progress reports on research into the generation of textile waste, its detailed classification, the global textile market, and the environmental impacts of waste textiles. The various challenges in textile waste management and the application of techniques of upcycling waste textiles are critically examined and ways of utilising waste textiles to produce upcycled products are explored.